Pengaruh Literasi Ekonomi Kreatif Generasi Z Pada Kerajinan Warangka Dan Hulu Keris Terhadap Transformasi Ekonomi Lokal (Studi Kasus: Desa Aengbajaraja Kabupaten Sumenep) - Dwi Putri Nor Hamidah; Afdhalul Izat; Ahmad Zaki Fuadi; Farahdilla Kutsiyah (CV. ITTC INDONESIA, 2026)
Warangka and Hulu Keris craft in Aengbajaraja Village, Sumenep Regency were part of the local cultural heritage that had great potential in the development of the creative economy. However, the utilization of this potential was still not optimal due to production and marketing patterns that tended to be traditional and the low understanding of the younger generation toward the culture based creative economy. This study aimed to analyze the influence of generation z creative economy literacy on local economic transformation in warangka and hulu keris crafts, This study used a quantitative approach with a descriptive associative research type. The study population consisted of all generation z craftsmen in Aengbajaraja Village with a saturated sampling technique involving 30 respondents. Data werw collected through a likert scale questionnaire and were analyze using the t test, F test, and coefficient of determination with SPSS. The results showed that creative economy literacy had a positive and significant effect on local economic transformation with a regression coefficient of 0.337 and a significance value of 0.022. the coefficient of determination value of 0.319 indicated thet creative economy literacy contributed 31.9% to local economic transformation. This transformation was reflected in the increase in design innovation, digital utilization, and the added value of cultural products. This study concluded that creative economic literacy was a crucial factor in driving economic chage based on local culture. The novelty of this research lay in its focus on the role of generation z in local economic transformation based on Madura keris culture, which had rarely been studied empirically.